KARAKTERISASI FISIK LIP BALM DENGAN EKSTRAK BIJI KURMA SEBAGAI ANTIOKSIDAN DAN PEWARNA ALAMI BUNGA BATAVIA - Muhammad Alfian; Muhammad Nurul Hasanudin; Askina Khoirun Nisa; Hisba Cahyani Irawan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
The growing demand for cosmetics within the community has spurred innovation in the use of herbal ingredients. Lip balm is one such cosmetic product that can benefit from the incorporation of natural components, including antioxidant compounds and natural dyes. This study aims to formulate a lip balm by integrating date seed extract as an antioxidant and batavia flower extract as a natural dye. The extraction process utilizes the maceration method with 96% ethanol as the solvent, followed by assessing the antioxidant activity through the DPPH method. Variations in the concentration of batavia flower extract in the lip balm formulation are set at 1.2%, 2.5%, and 3.7%, with a fixed date seed extract concentration of 2.5%. The evaluation of the lip balm's quality includes organoleptic tests, homogeneity tests, melting temperature tests, and pH tests. The antioxidant activity test on date seed extract yielded an IC50 value of 30.92 ppm, indicating a classification of strong antioxidant activity. The results for the three lip balm formulations exhibited consistent characteristics, including a pink color, a semi-solid consistency, a pH level range 6.5–6.7, and a melting point within the recommended range (52–57°C). In conclusion, the lip balm formulation incorporating date seed extract and batavia flower extract meets acceptable physical parameters for a lip balm product.